Change in Livestock patterns, adaptation strategies and Livelihood Security of the farmers affected by National Calamity in Bihar, India - lal, sudhanand Prasad (Indian Journal of Dairy Science, 2014)
Our research should be focused for those, who need it â€˜the utmostâ€™. So, the present study was conducted on 18th August 2008 victims of Kosi flood, whose primary or subsidiary occupation was Livestock rearing or Agriculture. The flood was declared as â€œNational Calamityâ€ by Prime minister of India on 28th August 2008 and so far it is the single calamity in the history of India to be officially declared as a â€œNational Calamityâ€. The present study was conducted in the purposively selected â€˜2008 floodâ€™ affected region of Bihar State. The data were solicited from 160 randomly selected farmers from two districts viz. Supaul and Madhepura because the extents of damage in these two districts were much higher than the other districts. The results indicate that there was a significant change in number of goat and poultry possessing farmers from year 2008 to 2014. There was a significant increase in Livestock population from mean value 2.98 to 4.48 with significant â€œZ-Valueâ€ of 6.99 at 1% level of significance, which consequently resulted in raise in milk production in litres/day from mean value 4.73 to 7.59; the value was also significant at 1% level with â€œZ-Valueâ€ of 11.37. Two prominent adaptation strategies were Inter/Intra-village group dynamics to attain livelihood security and Individual Produce, common marketing policy for attaining livelihood security. To measure the â€˜Livelihood Securityâ€™ of farmers, an Index was used, which revealed that majority of the respondents of the study area were having insecurity in terms of their Livelihood, as most of respondents happened to possess very low to medium (87.50%)Â  level of Livelihood security with overall mean value of 0.479.Â